The Dynamics of Marginalized Youth Not in Education, Employment, or Training Around the World - Levels, Mark; Brzinsky-Fay, Christian; Holmes, Craig; Jongbloed, Janine; Taki, Hirofumi (Routledge Studies in Labour Economics, 2022)
This book studies young people who are Not in Education, Employment, or Training (NEET); a prime concern among policymakers. Moving past common interpretations of NEETs as a homogeneous group, it asks why some youth become NEET, whereas other do not. The authors analyse diverse school-to-work patterns of young NEETs in five typical countries and investigate the role of individual characteristics, countries' institutions and policies, and their complex interplay. Readers will come to understand youth marginalization as a process that may occur during the transition from school, vocational college, or university to work. By studying longitudinal analyses of processes and transitions, readers will gain the crucial insight that NEETs are not equally vulnerable, and that most NEETs will find their way back to the labour market. However, they will also see that in all countries, a group of long-term NEETs exists. These exceptionally vulnerable young people are sidelined from society and the labour market. The country cases and cross-national studies illustrate that policies intended to help long-term NEETs to find their way in society are very limited. The book provides useful theoretical and empirical insights for scholars interested in the school-to-work transition and marginalized youth. It also provides helpful insights in vulnerability to policymakers who aim to combat youth marginalization.